Ecological and faunistic characteristics of the avifauna of the recreation zones of Minsk - Zhilkevich, Aliona V.; Svistun, Alena K. (Journal of the Belarusian State University. Ecology, 2019)
The study of the structure of bird communities is of great theoretical value. Almost universal distribution, relatively free movement, variety of trophic connections and complex spatial differentiation define birds as an important component of biocenoses. To determine how much impact the growth of urbanised territories in the animal community must regularly monitor progress. In this regard, in order to determine the degree of human influence on the ornithological community in urban conditions, an analysis of the population in three recreation areas of Minsk was carried out. The studies were conducted in the park Drozdy, Komsomol lake and the Loshitsa estate and park complex. As a result, it was found that the least susceptible to anthropogenic load park Drozdy and Loshitsa estate and park complex, which are located near the outskirts of the city. This is confirmed by the fact that there recorded the largest number of species (46 and 39, respectively), high density of birds and the highest value of the index of species diversity. Komsomol lake is located in the center of Minsk and is highly susceptible to anthropogenic and man-made load. The number of species equal to 22, low population density and low value of the index of species diversity suggests that this area is unfavorable for the ornithological community.
Keywords: birds; avifauna; ecological status; ecological groups; density; species diversity